The new encyclopedia britnannica in 30 volume, macropedia Volume 4 / William Benton - Benton, William (Estados Unidos de América: Encyclopedia Británica, Inc, 2001)
Colonization and the spread of Buddhism, the classical age, political changes, economic changes, the Portuguese in Ceylon, Buddhism and society, Dutch rule in Ceylon, the British in Ceylon , constitutionalism and nationalism, murals other works, historical development, structural elements, repertories, general features.
Ilustración, mapa, tabla
Col. Enc
Keywords: 1. ENCICLOPEDIA 2. ENCYCLOPEDIA BRITANNICA-MACROPEDIA VOL.4 3. REFERENCIA